Everything is politics: Understanding the political dimensions of NGO legitimacy in conflict-affected and transitional contexts - Oliver Walton (University of Bath, Centre for Development Studies (CDS), 2013)
This paper examines how national NGOs operating in conflict-affected or transitional regions generate and maintain legitimacy. It considers the experience of NGOs in three such contexts - Sri Lanka, Nepal and the Occupied Palestinian Territories (OPT). The paper argues that existing accounts of NGO legitimacy are unhelpful for understanding the dynamic and highly politicised processes of NGO legitimation that can be observed in these contexts and argues that greater attention should be paid to the contextual and political dimensions of NGO legitimation and de-legitimation.
Keywords: 330; NGOs; Legitimacy; Conflict; Sri Lanka; Nepal; Occupied Palestinian Territories (OPT)